Biventricular longitudinal strain as a predictor of functional improvement after D-shant device implantation in patients with heart failure - Zhou, Yi; Li, He; Fang, Lingyun; Wu, Wenqian; Sun, Zhenxing; Zhang, Ziming; Liu, Manwei; Liu, Jie; He, Lin; Chen, Yihan; Xie, Yuji; Li, Yuman; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The creation of an atrial shunt is a novel approach for the management of heart failure (HF), and there is a need for advanced methods for detection of cardiac function response to the interatrial shunt device. Ventricular longitudinal strain is a sensitive marker of cardiac function than conventional echocardiographic parameters. The data regarding the usefulness of longitudinal strain in the prediction of cardiac functional improvement after the implantation of interatrial shunt device are scarce. We aimed to investigate the exploratory efficacy of the D-Shant device of interatrial shunting for treating heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF), and explore the predictive value of biventricular longitudinal strain in such patients. Methods: A total of 34 patients were enrolled (25 with HFrEF and 9 with HFpEF). All patients underwent conventional echocardiography and two-dimensional speckle tracking echocardiogram (2D-STE) at baseline and 6 months following D-Shant device (WeiKe Medical Inc., WuHan, CN) implantation. Left ventricular global longitudinal strain (LVGLS) and right ventricular free wall longitudinal strain (RVFWLS) were evaluated by 2D-STE. Results: The D-Shant device was successfully implanted in all cases without periprocedural mortality. At 6-month follow-up, there was an improvement in New York Heart Association (NYHA) functional class was identified in 20 of 28 patients with HF. Compared with baseline, patients with HFrEF showed significant reduced left atrial volume index (LAVI) and increased right atrial (RA) dimension as well as improved LVGLS and RVFWLS at 6-month follow-up. Despite of reduced LAVI and increased RA dimension, improvements in biventricular longitudinal strain did not occur in HFpEF patients. Multivariate logistic regression demonstrated that LVGLS (odds ratio [OR]: 5.930; 95% CI: 1.463-24.038; P = 0.013) and RVFWLS (OR: 4.852; 95% CI: 1.372-17.159; P = 0.014) were predictive of NYHA functional class improvement after D-Shant device implantation. Conclusion: Improvements in clinical and functional status are observed in patients with HF at 6 months after the implantation of D-Shant device. Preoperative biventricular longitudinal strain is predictive of improvement in NYHA functional class and may be helpful to identify patients with improved outcomes after implantation of interatrial shunt device.